Whole-Face Approach with Hyaluronic Acid Fillers - Lipko-Godlewska S; Bolanča Ž; Kalinová L; Kermen I; Onisak B; Papp I; Rebrov M; Valančienė G (Dove Medical Press, 2021)
Sylwia Lipko-Godlewska,1 Željana Bolanča,2,3 Lucie Kalinová,4 Irēna Kermen,5 Boris Onisak,6 Ildikó Papp,7 Margarita Rebrov,8 Greta Valančienė9 1Private Practice, Cracow, Poland; 2University Clinical Hospital Center “Sestre Milosrdnice”, Zagreb, Croatia; 3Private Clinic Milojević, Zagreb, Croatia; 4Nemocnice Bulovka, Praha, Czech Republic; 5Private Practice, Riga, Latvia; 6Nobilis, Maribor, Slovenia; 7Koruti Orvosesztetikai Centrum, Budapest, Hungary; 8East-Tallinn Central Hospital, Tallinn, Estonia; 9Private Practice, Kaunas, LithuaniaCorrespondence: Sylwia Lipko-GodlewskaPrivate Practice, 30th Kasztelanska St., No. 2, Cracow, 30-116, PolandTel +48 660 483 865Email sgodlewska@gmail.comAbstract: The use of hyaluronic acid fillers in aesthetic medicine has changed over the years and the procedure became one of the most common in the world. Understanding the ageing process of the face and the anatomical interrelationships in the face have dramatically influenced the use of the hyaluronic acid fillers and the assessment of the patient. It was supported by a new technology of products and by the delivery of tools (eg, blunt cannulas), face imaging, and innovative injection techniques. The whole-face approach challenges the practitioner to look at the face as a whole, and the patient to trust and rely on the treatment plan. Over the years, we have understood, that the most important outcome of aesthetic procedures is what does the whole face look like not static but in motion, and how do people read emotions from it. Nowadays, the result changes “the face information” and makes aesthetic procedures more satisfactory. In this manuscript, we reviewed essentials of the current treatment approach including patient’s consultations, product selection and injection techniques used in different parts of the face. One size fits none; thus, we provided a general overview of hyaluronic acid fillers used in different indications and presented several treatment approaches to each region of the face.Keywords: hyaluronic acid, whole-face approach, aesthetic medicine